Sosialisasi Dan Pemberdayaan Tanaman Obat Keluarga Sebagai Penangkal Radikal Bebas Dari Polusi Udara Di Komplek Permata Biru Rt 06 Rw 23 Desa Cinunuk Kec Cileunyi Kab Bandung: Sosialisasi Dan Pemberdayaan Tanaman Obat Keluarga Sebagai Penangkal Radikal Bebas Dari Polusi Udara Di Komplek Permata Biru Rt 06 Rw 23 Desa Cinunuk Kec Cileunyi Kab Bandung - Ika Kurnia Sukmawati Ika (Jurnal Pengabdian IKIFA, 2023)
Air pollution is a problem experienced by developing countries. This occurs especially in urban areas with high levels of urbanization and increased industrial activity and traffic. This community service was carried out at RT 06 RW 23 Permata Biru Complex, Cinunuk Village, Cileunyi District, Bandung Regency. This housing complex has a fairly high population density, which increases other sectors such as industry and transportation, resulting in air pollution and reducing environmental quality. To overcome this problem, the Bhakti Kencana University Community Service team provides education and training in improving the immune system to prevent respiratory diseases by empowering Family Medicinal Plants (TOGA). The methods used in implementing the service include socialization, education about ISPA and the Utilization of Family Medicinal Plants (TOGA), TOGA planting demonstrations and the creation of a Family Medicinal Plant garden. The result is an increase in residents' knowledge about ISPA and the use of family medicinal plants, as evidenced by the average test score from 75 to 96. There is also the availability of land or family plantations that can be managed and utilized by the community. Keywords: TOGA, ISPA, Socialization,